2016
DOI: 10.1016/j.anbehav.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A preference to bond? Male prairie voles form pair bonds even in the presence of multiple receptive females

Abstract: Pair bonds are the cornerstone of a monogamous relationship. When individuals of the same species engage in monogamy and promiscuity (i.e. alternative reproductive tactics) it can be difficult to determine which tactic confers greater fitness, as measures of fitness can be difficult to ascertain. However, in these circumstances, whether animals preferentially establish pair bonds can reveal decisions that presumably reflect the animals’ assessment of how to best maximize reproductive success. In nature, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 55 publications
(93 reference statements)
1
35
1
Order By: Relevance
“…It is worth noting that the specific manipulation in the enriched context exposed males to three pairs of unrelated males and no females, potentially signaling that opportunities for bonding are low and that remaining single and mating opportunistically is the best possible avenue to maximize reproductive success. This hypothesis is consistent with the idea that non‐bonded prairie voles in nature might ‘choose’ to remain single and mate opportunistically based on the social context (Ophir, ; Ophir et al, ; Phelps & Ophir, ; Solomon & Jacquot, , but see Blocker & Ophir, ). It would also suggest that early life social experiences impact the neural mechanisms that subserve the decision to adopt particular reproductive tactics, or at least place males on trajectories that bias them to succeed within a given reproductive tactic (Okhovat et al, ; Ophir et al, ; Ophir et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…It is worth noting that the specific manipulation in the enriched context exposed males to three pairs of unrelated males and no females, potentially signaling that opportunities for bonding are low and that remaining single and mating opportunistically is the best possible avenue to maximize reproductive success. This hypothesis is consistent with the idea that non‐bonded prairie voles in nature might ‘choose’ to remain single and mate opportunistically based on the social context (Ophir, ; Ophir et al, ; Phelps & Ophir, ; Solomon & Jacquot, , but see Blocker & Ophir, ). It would also suggest that early life social experiences impact the neural mechanisms that subserve the decision to adopt particular reproductive tactics, or at least place males on trajectories that bias them to succeed within a given reproductive tactic (Okhovat et al, ; Ophir et al, ; Ophir et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…Despite extensive literature on intraspecific agonistic behaviors for rodents of the Northern Hemisphere (e.g., Sadleir 1965, Scott 1966, Munger & Brown 1981, Wolff et al 1983, Petersen & Helland 2015, Blocker & Ophir 2016, few studies have been conducted on sigmodontine rodents (e.g., Courtalon et al 2003, Steinmann et al 2009, Bonatto et al 2013a, Petersen & Helland 2015, Bonatto et al 2017. Furthermore, this is the first study that reports intraspecific killing in free-living sigmodontines trapped in the same live-trap.…”
Section: ____________________________________________________________mentioning
confidence: 94%
“…During behavioral observations of the dry vesper mouse Calomys musculinus (Rodentia, Cricetidae), males did not demonstrate aggressiveness during the breeding season, in contrast to females, that are territorial (Steinmann et al 2009). Surprisingly, male prairie voles Microtus ochrogaster (Rodentia, Cricetidae) are more aggressive to females in general after they bond to one, even if they are sexually receptive (Blocker & Ophir 2016).…”
Section: ____________________________________________________________mentioning
confidence: 99%
“…Like humans, prairie voles are designated as a socially monogamous species because the adult male and female pairs show a preference to live together but do not mate exclusively (Carter et al, 1995;Strassmann, 2003;Solomon et al, 2004;Streatfeild et al, 2011). Laboratory studies have shown that when male prairie voles are given the opportunity to access multiple mates, they show a preference to mate with only one of them (Blocker and Ophir, 2016). Although pair-bonded males are attentive to the sensory stimuli of other sexually-receptive females (Parker et al, 2011;Rodriguez et al, 2013), when given a choice, they prefer to remain in contact with their mate rather than a novel female (Blocker and Ophir, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory studies have shown that when male prairie voles are given the opportunity to access multiple mates, they show a preference to mate with only one of them (Blocker and Ophir, 2016). Although pair-bonded males are attentive to the sensory stimuli of other sexually-receptive females (Parker et al, 2011;Rodriguez et al, 2013), when given a choice, they prefer to remain in contact with their mate rather than a novel female (Blocker and Ophir, 2016). This suggests that males may be predisposed to forgo a desire to seek other mates once they form a pair bond.…”
Section: Introductionmentioning
confidence: 99%